NATURAL GYNECOLOGY: THEORY AND PRACTICE - Eduarda de Araújo Torres, Ana; Patrícia de Oliveira, Alcina; Conceição de Assis, Jefferson; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
Feminism plays an important role in the construction and deconstruction of gynecology. From the distance it brought for women to enter the job market more effectively, to the return to the search for self-knowledge, which includes their own body. The holistic nurse, or specialist therapist in the area, will check the exams, take an anamnesis with the patient to try to find out the reason for the consultation and seek treatment as a whole. Some activities can be prescribed such as phytotherapy with the use of flower remedies, Reiki, acupuncture, meditation, uterine vaporization. With this, a multidisciplinary team will be activated to accompany this woman and generate the greatest possible comfort.